PENGARUH KEGIATAN ORANG MUDA KATOLIK BAGI PERKEMBANGAN IMAN (KAUM MUDA) DI PAROKI ST. FRANSISKUS ASISI RESAPOMBO - Sari, Chatarina Prischa Laras; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
Young Catholics are those who have Faith in God through Jesus Christ guidance of the Holy Spirit in the communion of Catholic churches. Young Catholics are the next generation of the church, the future of the church, and the pillar of the church. Young catholics have such activities as: retreats, recollection, Eucharists, pilgrims, and other. The activities of the young Catholic aimed to develope faith, drawing closer to God, and making themselves increasingly positive. To what extent do young people beome involved in such activities? How For the activities of young catholics develop faith? The study uses a quallitative method. This study was carried out on 3-9 october 2019. Respondents of this study were young Catholics 13-30, actively engaged in action in St. Francis’s Parish of Resapombo, and easy to meet. The number of respondents in this study is 9. According to research, 9 respondents (100%) can explain the activities of young catholics. All other, 9 respondents (100%) are able to answer or define a growing sense of faith. Related to the influence of young catholics’ activities for the development of faith in Sr. Francis’s Parish of Resapombo, 8 respondents (88,8%) saw the effect that young catholics’ activities had on the development of faith, and 1 respondent (11,1%) said that young catholics’ activities had no effect on the development of faith.